A new diffractometer for diffuse scattering studies on the ID28 beamline at the ESRF. (13th December 2018) - Girard, A.; Nguyen-Thanh, T.; Souliou, S. M.; Stekiel, M.; Morgenroth, W.; Paolasini, L.; Minelli, A.; Gambetti, D.; Winkler, B.; Bosak, A.
Abstract : A new diffractometer has been built as a side station on the ID28 beamline at the ESRF. The instrument is primarily dedicated to the study of diffuse scattering in a large class of materials, ranging from strongly correlated electron systems to nanoscale‐modulated and low‐dimensional systems. Abstract : A new diffractometer is now available to the general user community at the ESRF. The new diffractometer is a side station of the high‐resolution inelastic X‐ray scattering spectrometer on beamline ID28 and is located in the same experimental hutch. Both instruments can be operated simultaneously. The new diffractometer combines a fast and low‐noise hybrid pixel detector with a variable diffraction geometry. The beam spot on the sample is 50 µm × 50 µm, where focusing is achieved by a combination of Be lenses and a KB mirror. Wavelengths from 0.5 to 0.8 Å can be used for the diffraction experiments. The setup is compatible with a variety of sample environments, allowing studies under non‐ambient conditions. The diffractometer is optimized to allow a rapid survey of reciprocal space and diffuse scattering for the identification of regions of interest for subsequent inelastic scattering studies, but can also be employed as a fully independent station for structural studies from both powder and single‐crystal diffraction experiments. Several software packages for the transformation and visualization of diffraction data are available. An analysis of data collected with the new diffractometer shows that the ID28 side station is a state‐of‐the‐art instrument for structural investigations using diffraction and diffuse scattering experiments.